1986
DOI: 10.1086/164781
|View full text |Cite
|
Sign up to set email alerts
|

General constraints on the age and chemical evolution of the Galaxy

Abstract: The formalism of Schramm and Wasserburg (1970) for determining the mean age of the elements is extended. Modelindependent constraints (constraints that are independent of a specific form for the effective nucleosynthesis rate and Galsct,ic chemical evolution over time) are derived on the first four terms in the expansion giving the mean age of the elements, and from these constraints limits are derived on the total duration of nucleosynthesis. These limits require only input of the Schramm-Wasserburg parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…There are a few other works which investigated the same quantities from radiative cross sections [3]. The (n, γ) cross sections can also be used in the study of nuclear cosmochronology to determine the age of the Galaxy [10][11][12]. Though the neutron capture cross sections, in gen-3 eral, have 1/v dependence, this can significantly differ when the p-wave capture is superimposed on pure swave contribution, thus resulting in an increase in the cross-section values with incident neutron energy.…”
mentioning
confidence: 99%
“…There are a few other works which investigated the same quantities from radiative cross sections [3]. The (n, γ) cross sections can also be used in the study of nuclear cosmochronology to determine the age of the Galaxy [10][11][12]. Though the neutron capture cross sections, in gen-3 eral, have 1/v dependence, this can significantly differ when the p-wave capture is superimposed on pure swave contribution, thus resulting in an increase in the cross-section values with incident neutron energy.…”
mentioning
confidence: 99%
“…Typical estimates for the Galaxy's (and Universe's) age as determined from cosmochronology are of the order of 9.6 Gyr (e.g. Meyer and Schramm 1986). In recent years questions about the role of &delayed fis-sion in estimating actinide production ratios 89 well as uncertainties in is7Re decay due to thermal enhancement and the discussion of Th/Nd abundances in stars have obfuscated some of the limits one can obtain.…”
Section: Nucleocosmochronologymentioning
confidence: 99%
“…To extend these mean age limits to a total age limit requires some galactic evolution input. However, as Peeves and Johns (1976) first showed, and as Meyer and Schramm (1986) developed further, one can use chronometers to constrain Galactic evolution models and thereby further restrict the age from the simple mean age limits of Schramm and Wasserburg. To try to push further on such ranges and give ages to fl Gyr accuracy, as some authors have done, always necessitates making some very explicit assumptions about Galactic evolution beyond the pure chronometric arguments.…”
Section: Nucleocosmochronologymentioning
confidence: 99%
“…Meyer and Schramm (25), extending the early work by Schramm and Wasserburg (26), sought to provide a modelindependent age determination. In the limit of long-lived chronometers (T Ͻ Ͻ 1), they derive a simple expression for the age that is approximately independent of galactic evolution effects.…”
mentioning
confidence: 99%
“…The history of star formation and nucleosynthesis activity thus becomes a significant consideration. It was the recognition of this constraint that led Meyer and Schramm (25) to the determination of a lower bound (T ϩ SS ) Ͼ 9.6 Gyr. These authors also concluded that ''the effective nucleosynthesis rate was relatively constant over most of the duration of nucleosynthesis.…”
mentioning
confidence: 99%